The progress of the regional GDP in the regions of the Czech Republic with regard to the methodological aspects - Monika Nováková; Luděk Kouba (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
The regional GDP is used in the European Union as the important indicator to the distribution of the European funds. However in the Czech Republic this indicator has had only a short history because regional GDP started to be constructed in the half of the ninetieth. The aims of the paper are to present and evaluate the progress in the process of the regionalization of the GDP in the Czech Republic, review economic productivity of the Czech regions (level NUTS 2 and NUTS 3) and finally point out the persisting weaknesses of the regionalization of the GDP in the Czech Republic. First part of the paper describes problematic beginnings of the process of the regionalization of the GDP, evaluates changes of the methodology and discusses the actual state of this affair. Second part of the paper describes the variability of GDP among the Czech regions at level NUTS 2 and NUTS 3. Alternative modifications of the indicator GDP (for example GDP, GDP per capita, rate of growth) are used in this regional analysis. Consecutively relative positions of individual regions in the Czech Republic are discussed. There are pointed out some contradictions in the Czech regional statistics in this paper. The defined drawbacks indicate possible way of the research into the future.